Commercialization process of digital service offerings in manufacturing firms - Kieu, Nhi (My University, 2026)
Manufacturing firms have been increasingly developing digital service offerings as a means of creating new customer value beyond traditional product-based competition. These offerings emerge at the intersection of service innovation and digital technologies, where value is created through continuous, data-driven interactions between providers, customers, and broader ecosystems. However, many struggle to translate their development efforts into sustainable financial performance due to shortcomings in commercialization rather than technical development. Commercialization is still frequently treated as a final market launch step rather than as a sustained, multi-phase process. Existing research has concentrated on capability development and performance outcomes, leaving the commercialization process itself underexplored, particularly in terms of how it unfolds over time across phases, barriers, and actor configurations. This thesis addresses this gap by adopting a process-oriented perspective and examining how the commercialization of digital service offerings develops in practice. A qualitative single case study of KONE Corporation, a global leader in the elevator and escalator industry, was conducted using publicly available documentary sources covering the period from 2016 to 2026. The findings show that commercialization unfolded across three overlapping phases in a non-linear manner: (1) concept and value proposition validation, (2) business model validation and market formation, and (3) scaling through ecosystem integration. Within the process, barriers shift forms rather than disappearing across phases, management capabilities expand progressively, and a persistent tension between value creation and value capture grows more structurally complex as the offering becomes more ecosystem-based. The study contributes a more dynamic understanding of digital service commercialization, where managing it requires not only building capabilities and partnerships, but actively governing how the commercial object itself is redefined as offerings grow more distributed across partner ecosystems.
Keywords: commercialization process; innovation process; service innovation; digital service offering